(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Mobile Adhoc Networks are more vulnerable because in the (MANET) Mobile Adhoc Network all node works as data sink, transmitter, router. There is no centralized system in the Mobile Adhoc network, so the chances of the vulnerabilities are very high in the network. There are various security issues in the Mobile Adhoc Network. From the various attacks the flooding attacks are most difficult attacks that extremely affect in Mobile Adhoc Network. In this paper, a new statistical based technique is planned, which is used to discover the flooding attack in an positive approach than other approaches. In the planned of Statistical Ad-Hoc on Demand Distance Vector (SAODV) approach is used to detect malicious nodes in the Mobile Adhoc Network. In this technique, statistical threshold value is obtained from mean and variance. In this approach the value is utilize to locate the (RREQ) Route Request flooding attacker nodes in the Mobile Adhoc Network. The proposed method is capable because threshold values are calculated on the source of RREQs prepared by every node in the Mobile Addhoc Network. The simulation results clearly depict that the proposed approach has significant performance in the terms of throughput, delay, packet delivery ratio, and overhead.